Mem?ria hist?rica de implanta??o do programa SWAP-Bahia na perspectiva da auditoria do sistema ?nico de sa?de: um estudo documental - Lima, Jean Carla de (2021)
The SWAP-Bahia Program is an intersectoral public policy and external public funding, with the aim of contributing to the improvement of the population's quality of life in the areas of maternal and child health, and also in the institutional modernization of the areas involved. . Auditing SUS Bahia, in addition to auditing, inspection and control, developed a relevant regulatory role in the program implementation process. The objective was to describe the implementation process of the SWAP-BAHIA Program from the perspective of the SUS Bahia Audit, in the period 2008-2012 and to present the historical memory of the implementation of this Program in the State of Bahia. A qualitative documentary research was carried out, the result of a concrete experience that took place in the State of Bahia, referring to an intersectoral public policy and external public funding, the SWAP-Bahia Program. For data analysis, the following steps were used: verification and organization of the material, based on a reading, using criteria of content analysis and critical analysis of documents ? characterization, description and comments; filing; survey of recurring issues; codification; emerging core evidence; decoding, interpretation and inference. The results of this research are presented from the following categories: implementation process of the SWAP-Bahia Program, from the perspective of the SUS-Bahia Audit, in the period 2008-2012: reduction of infant and neonatal mortality and improvement of the quality of health care provided to pregnant women and newborns; and historical memory of the implementation of the SWAP-Bahia Program in the State of Bahia: strengthening the institutional capacity for auditing the Unified Health System. It can be concluded that promoting cooperation between the Health Sector and the Water Sector is an efficient strategy to reduce infant mortality and morbidity, which corroborates the objectives of the SWAP-Bahia. Adequate water supply and sanitation, access to primary health care services, and rotavirus vaccination are extremely important for preventing infectious intestinal diseases and reducing infant mortality. Quality health services are crucial for the reduction of neonatal mortality and by quality we mean: better equipment; timely referrals from primary care health services to more complex services (health regulation); and better health care in the area of ??obstetrics and training. This research allowed a SUS internal control body, the SUS-Bahia Audit, to describe its experience in an intersectoral public policy and external financing, the SWAP-Bahia Program, and seeks to contribute to the institutional strengthening of the body.